ANALISIS DUKUNGAN ORANG TUA DALAM MOTIVASI BELAJAR ANAK KELAS III PADA MATERI MENULIS SURAT PRIBADI - Yulaeha, Wiwin; Kusuma Putri, Mega; Hetilaniar (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research was motivated by the phenomenon of low interest in writing among third-grade students, who often view personal letters as a tedious academic burden. The primary objective of this study was to examine in depth how parental support, both material and non-material, can act as a catalyst in motivating students to learn. Through a qualitative approach using observation and interviews, the results revealed that emotional parental support such as guidance in sentence construction and appreciation for work has a more significant impact than simply providing stationery. When parents are actively involved in their children's creative process, psychological barriers to writing can be minimized, allowing students to become more expressive and confident in composing personal letters. These findings confirm that literacy success at the elementary level is not solely a product of teacher instruction in the classroom, but rather the result of warm synergy in the family room.